2005
DOI: 10.1007/s10549-005-9056-0
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant use and breast cancer risk

Abstract: Based on these results and those of previous studies, there is limited evidence that any type of antidepressant use is associated with breast cancer risk overall. SSRIs may elevate risks of PR- and ER+/PR- tumors, though further studies are needed to confirm these associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
36
8
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 25 publications
9
36
8
1
Order By: Relevance
“…Similar to our study, most prior studies have found little or no association with ever use of antidepressants (all classes combined) For use of tricyclic antidepressants, no increased risks were seen in most studies for current (Chien et al, 2005;Gonzalez-Perez and Garcia Rodriguez, 2005) or ever use (Kelly et al, 1999;Cotterchio et al, 2000;Wang et al, 2001;Sharpe et al, 2002;Moorman et al, 2003;Steingart et al, 2003;Chien et al, 2005). In the present study, there was a weak positive association when adjusted only for matching factors and this was attenuated when adjusted for additional potential confounders.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Similar to our study, most prior studies have found little or no association with ever use of antidepressants (all classes combined) For use of tricyclic antidepressants, no increased risks were seen in most studies for current (Chien et al, 2005;Gonzalez-Perez and Garcia Rodriguez, 2005) or ever use (Kelly et al, 1999;Cotterchio et al, 2000;Wang et al, 2001;Sharpe et al, 2002;Moorman et al, 2003;Steingart et al, 2003;Chien et al, 2005). In the present study, there was a weak positive association when adjusted only for matching factors and this was attenuated when adjusted for additional potential confounders.…”
Section: Discussionsupporting
confidence: 82%
“…Antidepressant use has increased steadily (Stafford et al, 2001;Pirraglia et al, 2003;Meijer et al, 2004) since the introduction of selective serotonin reuptake inhibitors (SSRIs) in the late 1980s, with use reported by 10 -20% of women in recent studies (Moorman et al, 2003;Steingart et al, 2003;Chien et al, 2005), though actual use is likely to be higher due to underreporting (Boudreau et al, 2004).…”
mentioning
confidence: 99%
“…Conflicting results of antidepressant use and de novo cancer risk have been reported [264][265][266][267][268][269][270]. A case-control study found no association between antidepressant use and breast cancer risk; a protective effect of paroxetine hydrochloride was observed in subjects who were not overweight [264].…”
Section: Antidepressant Usementioning
confidence: 99%
“…This variation may be attributed to the types of breast cancer. SSRIs increased the risk of PR-and ER+/PR tumors, but not other types of breast cancer [266]. The association between antidepressants and breast cancer are mixed in the preclinical and clinical data.…”
Section: Antidepressant Usementioning
confidence: 99%
See 1 more Smart Citation